Optimización de los procesos de mezclado de balanceado; para aves de postura en la avícola Avimar en la provincia de Cotopaxi. generando el mejoramiento de la productividad durante el periodo 2020 – 2021. - Martínez Brito, Milton Danilo (2021)
AVIMAR is a poultry company in the city of Salcedo in the province of Cotopaxi with more than 10 years in the market that is constantly growing. This is a poultry industry dedicated to the production of balanced, activities aimed at feeding laying hens (white hills and red hills). Within the balanced mixing process, unproductive and repetitive times are identified that generate delays caused by inadequate operation, incorrect distribution of space and the lack of machinery that affects the execution of normal activities related to its elaboration; These problems limit the production capacity and for which an analysis of the current situation of the process was carried out through direct observation where the activities involved in the balanced production process are identified, in order to improve productivity and cover the demand for balancing, which is needed for the 10,000 birds that are projected to be introduced in the poultry farm, for this a study of current times and movements in the mixing process was carried out to determine the standard time of the process of the area where the study is carried out . Achieving the reduction of the mixing time from 29.36 (min) to 22.74 (min) per cycle; since with these optimized times the increase in production cost is avoided. With the improvements and implementations carried out, the increase in the efficiency of the production force is evidenced and for this reason productivity was increased by 29.12%. This type of study is of utmost importance for continuous improvement as it helps to optimize the time required for project execution, minimize costs and provide a more reliable and high-quality product.